Forest status and forestry stakeholder analysis for low-emission food systems in Nandi, Kenya - Mutune, Jane M.; Pham, Thu Thuy; Nguyen, Duc Tu; Tran, Ngoc My Hoa; Nguyen, Thi Van Anh; Nguyen, Thi Thuy Anh; Nguyen, Trung Son; Nguyen, Dinh Yen Khue; Dibo, Duba; Elmah, Odhiambo; Kahuha, Francis (CIFOR-ICRAF, 2023)
This report provides an overview and profile of the forestry sector and stakeholders in Nandi County, Kenya, and how they can contribute to low-emission food systems in the region. It also presents Nandi forestry stakeholders’ views on challenges to, and opportunities for forestry-based mitigation options. The study employed both quantitative and qualitative methods by collecting and analysing primary and secondary data. Primary data was collected from in-depth interviews with key informants, and focus group discussions (FGDs). A structured questionnaire was used for key informant interviews. Secondary data was derived from previous publications and gray literature on the forestry sector.